TREATMENT OF LOWER URINARY TRACT SYMPTOMS CAUSED BY DOUBLE J STENT WITH SOLIFENACIN AND COMBINATION OF TAMSULOSIN PLUS SOLIFENACIN: A COMPARATIVE STUDY - Hanan Noor; Nauman Khalid; Muhammad Sohail et al. (Journal of University Medical & Dental College, 2018)
ABSTRACT: OBJECTIVE: To compare the mean change in international prostate symptom score (IPSS) by combination therapy of Tamsulosin and Solifenacin with Solifenacin alone in treatment of lower urinary tract symptoms (LUTS) caused by double J (DJ) stents. STUDY DESIGN: Randomized control trial PLACE AND DURATION OF STUDY: Urology Department, Madinah Teaching Hospital Faisalabad, from December 2015 to June 2016. METHODOLOGY: Total 170 patients having LUTS after DJ stent insertion were selected for the study. DJ stenting was done in these patients before extra-corporeal shock wave lithotripsy (ESWL), following ureterorenoscopy (URS) and intracorporeal lithotripsy, percutaneous nephrolithotomy (PCNL), ureterolithotomy, pyelolithotomy, pyeloplasty and in patients with obstructive uropathy. All the patients were allocated two diﬀerent groups. Group A received Tamsulosin 0.4 mg and Solifenacin 5 mg daily & Group B received Solifenacin 5 mg once a day every stda y. The IPSS questionnaire was ﬁlled on 1 post-operative day and on 6th post-operative week. Final results were made on 6th post-operative week by comparing the mean change in IPSS in both groups. Independent sample t-test and paired t-test were applied. P-value < 0.05 was taken as signiﬁcant. RESULT: Mean age was 42.92+7.04 years in Group-A and 43.38+6.67 years in Group-B. Total number of male patients was 58 (68.24%) in Group-A and 52 (61.18%) in Group-B. Female patients in Group-A were 27 (31.76%) and 33 (38.82%) in Group-B. Mean IPSS was 9.01+1.29 in Group-A and 9.10+1.23 in Group-B at baseline (p=0.62). After 6 weeks IPSS was 4.69+0.89 in Group-A and 6.87+1.25 in Group-B (p=0.0001). The mean diﬀerence in IPSS after 6 weeks was 4.30+1.49 in Group-A and 2.23+1.13 in Group-B with p value 0.0001 reﬂecting a signiﬁcant diﬀerence between the two groups. CONCLUSIONS: The mean change in IPSS by combined treatment of Tamsulosin and Solifenacin was signiﬁcant when compared to Solifenacin alone in treatment of DJ stents related LUTS.